# Calculus

derivative of ((Sqrt(x+3y)+sqrt(3xy))=(sqrt(21)+sqrt(90)) at point (6,5)google

1. 👍 0
2. 👎 0
3. 👁 257
1. Check that (6,5) lies on the curve by substituting x=6,y=5 and see if the equality holds. (yes, it holds).

Differentiate:
((Sqrt(x+3y)+sqrt(3xy))=(sqrt(21)+sqrt(90))
(1/2)/sqrt(x+3y)*(1+3y')+(1/2)/sqrt(3xy)*(3y+3xy')=0
transpose and cross multiply:
-sqrt(x+3y)*(1+3y')=sqrt(3xy)*(3y+3xy')
Solve for y'

y'(x,y)=-(sqrt(3*y+x)+3^(3/2)*y*sqrt(x*y))/(3*sqrt(3*y+x)+3^(3/2)*x*sqrt(x*y))

so
y'(6,5)=(-5*3^(3/2)*sqrt(30)-sqrt(21))/(2*3^(5/2)*sqrt(30)+3*sqrt(21))
=-0.796....

1. 👍 0
2. 👎 0

## Similar Questions

1. ### algebra

Simplify: 2 sqrt (3) + 6 sqrt(2) - 4 sqrt(3) + sqrt (2) a) 8 sqrt(2) - 3 sqrt(3) b) 6 sqrt(2) - 8 sqrt(3) c) 5 sqrt(6) d) 7 sqrt(2) - 2 sqrt(3) the answer i picked was d

2. ### math-Inverse functions

f(x)=-4x-2 & g(x)=5x-6. Find (f*g) and state domain. f(x)-x^2-1 what is the equation for f^-1(x)? f(x)=3x+2, find f(f^-1(14)). f(x)=4x+7 and g(x)=3x-5 find (f*g)(-4) f(x)=sqrt x+3 what is equation for f^-1(x)? Graph y=sqrt x-2 +5

3. ### algebra

am I right? 1. Simplify radical expression sqrt 50 5 sqrt ^2*** 2 sqrt ^5 5 sqrt ^10 5 2. Simplify the radical expression sqrt 56x^2 28x 2x sqrt 14*** 2x sqrt 7 sqrt 14x2 3. Simplify the radical expression. sqrt 490y^5w^6 2 sqrt

4. ### Math

Which is the exact value of the expression sqrt 32- sqrt 50 + sqrt 128 2 sqrt 7 7 sqrt 2 22 sqrt 2 2 sqrt 55

1. ### Calculus

In these complex exponential problems, solve for x: 1)e^(i*pi) + 2e^(i*pi/4)=? 2)3+3=3i*sqrt(3)=xe^(i*pi/3) MY attempt: I'm not really sure of what they are asking. For the 1st one I used the e^ix=cos(x)+i*sin(x) and got

2. ### Calculus

show lim x->3 (sqrt(x)) = (sqrt(c)) hint: 0< |sqrt(x)-sqrt(c)|= (|x-c|)/(sqrt(x)+sqrt(c))

3. ### Calculus

show lim x->3 (sqrt(x)) = (sqrt(c)) hint: 0< |sqrt(x)-sqrt(c)|= (|x-c|)/(sqrt(x)+sqrt(c))

4. ### Algebra 2

Operations with Complex Numbers Simplify. 1. sqrt(-144) 2. sqrt(-64x^4) 3. sqrt(-13)*sqrt(-26) 4. (-2i)(-6i)(4i) 5. i13 6. i38 7. (5 – 2i) + (4 + 4i) 8. (3 – 4i) – (1 – 4i) 9. (3 + 4i)(3 – 4i) 10. (6 – 2i)(1 + i) 11.

1. ### linear algebra urgent

For the orthogonal matrix A = 1/sqrt(2) -1/sqrt(2) -1/(sqrt(2)) -1/sqrt(2) verify that (Ax,Ay)=(x,y) for any vectors x and y in R2. Can someone please explain this

2. ### Algebra

Which of these expressions is in simplified form? A. a ^3 sqrt 4 - b ^3 sqrt 2 / 2 B. sqrt 1/2x + sqrt 1/2z C. x^2 - 3x sqrt y / sqrt 3 D. sqrt 125x - x^2

3. ### algebra

simplify: square root of 5 + square root of 20 - square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20 - sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5) - sqrt (3*9) + sqrt (49*3) = 3 sqrt 5 - 3 sqrt 3 +

4. ### algebra

simplify: sqrt (28) a) 4 sqrt (7) b) 7 sqrt (2) c) 2 sqrt (7) d) sqrt (7) c im just making show that they are correct sorry for posting up so many